MicroRNAs as biomarkers of atrophic scarring in acne: a cross‐sectional analysis of 41 patients. (1st December 2021) - Ghumra, W.; Lee, N.; Whitehouse, H.; Bhutani, R.; Lagos, D.; Layton, A. M.
Summary: Background: Acne is the commonest inflammatory dermatosis seen worldwide. Atrophic acne scarring is a frequent complication, which can arise from acne of any severity. Micro (mi)RNAs are noncoding RNA molecules of 19–25 nucleotides that function as post‐transcriptomic mediators of gene expression. They have demonstrated differential expression in various pathologies, such as eczema and psoriasis, allowing for a unique miRNA 'signature' profile to be established for different disease states. Aim: To establish a miRNA signature for acne, and acne‐associated atrophic scarring and to identify if a pattern of circulating miRNA is evident in patients who are prone to scarring. Methods: In total, 41 participants were consecutively recruited to this study. Circulating miRNA was quantified from plasma samples in all 41 patients, while in 8 patients, and in a further validation cohort of 9 patients, whole miRNAome was undertaken from tissue specimens, which included lesional, normal and where present, scarred skin. Results: Three miRNAs, miR‐223, miR‐21 and miR‐150, were statistically significantly overexpressed in acne lesions, and notably, in clinically uninvolved skin in participants prone to scarring. In this subgroup, we also found statistically significantly elevated levels of circulating miRNA‐21 and miRNA‐150. Conclusion: The presence of elevated levels of these specific miRNAs in the serum of patients with acne raises the potential of a blood test to identify those at risk of scarring, allowing for earlier intervention with effective therapy.